Variable Sound Insulation Structure with MFC Elements - GÓRSKI, Paweł; KOZUPA, Michał (Archives of Acoustics, 2012)
Additional sound sources are used as actuators in the vast majority of active noise reduction systems.One of the possible opportunities to extend the field of applications of active noise reduction systems isusing active structures of variable sound insulation. The paper presents an analysis of ways of reducingnoise with a structure of variable sound insulation consisting of a metal plate, active elements (MacroFiber Composite), and a control system. The paper presents results of acoustic radiation simulations andmeasurements of sound intensity generated by the structure under the influence of stimulation by anacoustic wave. Simulations of mechanical vibrations and acoustic radiation for the plate were performedwith the finite element method and ANSYS software. Simulation results made it possible to select locationsfor gluing the active elements and sensors. Analyses of the sound pressure level in the space to whichthe plate is radiating made it possible to determine dominant frequencies in the characteristics and, asa result, indicate vibration modes that can be reduced. Sound intensity measurements were performedwith a three-way probe of USP mini Microflown. Results of simulations and measurements show that itis possible to achieve an improvement of the insulating power of a metal plate by approx. 10 dB.